2011
DOI: 10.3171/2010.8.jns10639
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative mapping and monitoring of the corticospinal tracts with neurophysiological assessment and 3-dimensional ultrasonography-based navigation

Abstract: Combining elaborate neurophysiological assessment, tractography-based neuronavigation, and updated IOUS images provided accurate localization of the CSTs and enabled the safe resection of tumors approximating these tracts. This is the first attempt to evaluate the distance from the CSTs using the threshold of subcortical monopolar stimulation with real-time IOUS for the correction of brain shift. The linear correlation between the distance to the CSTs and the threshold of subcortical stimulation producing a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
1
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(103 citation statements)
references
References 26 publications
3
91
1
7
Order By: Relevance
“…При маленькой силе тока (1-3 мА) при прямой субкортикальной ЭС только у 23 из 67 пациентов не отмечалось перма-нентных неврологических нарушений в послеопе-рационном периоде, что связано с большим объ-емом резекции у данной категории пациентов [39]. Как известно, сила тока имеет прямую взаимозави-симость с расстоянием, на которое он распростра-няется, с примерным соотношением 1 мм -1 мА («золотое правило» нейрофизиологии) [23,[40][41][42].…”
Section: Discussionunclassified
“…При маленькой силе тока (1-3 мА) при прямой субкортикальной ЭС только у 23 из 67 пациентов не отмечалось перма-нентных неврологических нарушений в послеопе-рационном периоде, что связано с большим объ-емом резекции у данной категории пациентов [39]. Как известно, сила тока имеет прямую взаимозави-симость с расстоянием, на которое он распростра-няется, с примерным соотношением 1 мм -1 мА («золотое правило» нейрофизиологии) [23,[40][41][42].…”
Section: Discussionunclassified
“…Although this correlation is still under discussion, the majority of neurosurgeons presume a linear correlation of 1 mA of stimulation equals approximately 1 mm of distance of the stimulation point to the CST. 64,76,78,88 Recently we published our own evaluation of the relation of stimulation distance and stimulation energy. These data revealed that the distance-to-energy relationship is not linear and that stimulation points are closer than assumed from the "1 mA resembles 1 mm" rule.…”
Section: Subcortical Mappingmentioning
confidence: 99%
“…76,83,88 Concerning this stimulation setup, Szelényi et al performed a highly cited and crucial study comparing train application with the single-pulse technique as well as bipolar and monopolar stimulation. 111 It was found that the CST is most efficiently identified using a multipulse train technique with a monopolar probe.…”
Section: Subcortical Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…We start with an initial stimulation intensity of 10-15 mA, which corresponds to about 10-15 mm from the CST. 16,27,28,30,38 The instant an MEP is elicited, the surgeon is immediately alerted by the change of the high-pitch negative control sound to a low-pitch alert sound. The stimulation intensity is then reduced in 2-mA steps, allowing the surgeon to continue tumor removal until another low-pitch alert sound indicates that resection is getting closer to the CST.…”
Section: Intraoperative Handling Of the Continuous Dynamic Mapping Dementioning
confidence: 99%